Dunia Melayu dan dunia Indocina - Ismail Hussein Datuk 1932-; Lafont, Pierre-Bernard (Dewan Bahasa dan Pustaka, Kementerian Pendidikan, Malaysia, 1995)
History of socio-cultural relations between Malay and Indochina; collection of articles.